Effects of a Feedback-Demanding Stroke Clock on Acute Stroke Management: A Randomized Study. Issue 10 (October 2020) - Fousse, Mathias; Grün, Daniel; Helwig, Stefan A.; Walter, Silke; Bekhit, Adam; Wagenpfeil, Stefan; Lesmeister, Martin; Kettner, Michael; Roumia, Safwan; Mühl-Benninghaus, Ruben; Simgen, Andreas; Yilmaz, Umut; et al.
Abstract : Background and Purpose: This randomized study aimed to evaluate whether the use of a stroke clock demanding active feedback from the stroke physician accelerates acute stroke management. Methods: For this randomized controlled study, a large-display alarm clock was installed in the computed tomography room, where admission, diagnostic work-up, and intravenous thrombolysis occurred. Alarms were set at the following target times after admission: (1) 15 minutes (neurological examination completed); (2) 25 minutes (computed tomography scanning and international normalized ratio determination by point-of-care laboratory completed); and (3) 30 minutes (intravenous thrombolysis started). The responsible stroke physician had to actively provide feedback by pressing a buzzer button. The alarm could be avoided by pressing the button before time out. Times to therapy decision (primary end point, defined as the end of all diagnostic work-up required for decision for or against recanalizing treatment), neurological examination, imaging, point-of-care laboratory, needle, and groin puncture were assessed by a neutral observer. Functional outcome (modified Rankin Scale) was assessed at day 90. Results: Of 107 participants, 51 stroke clock patients exhibited better stroke-management metrics than 56 control patients. Times from door to (1) end of all indicated diagnostic work-up (treatment decision time; 16.73 versus 26.00 minutes, P <0.001), (2) end of neurological examination (7.28 versus 10.00 minutes, P <0.001), (3) end of computed tomography (11.17 versus 14.00 minutes, P =0.002), (4) end of computed tomography angiography (14.00 versus 17.17 minutes, P =0.001), (5) end of point-of-care laboratory testing (12.14 versus 20.00 minutes, P <0.001), and (6) needle times (18.83 versus 47.00 minutes, P =0.016) were improved. In contrast, door-to-groin puncture times and functional outcomes at day 90 were not significantly different. Conclusions: This study showed that the use of a stroke clock demanding active feedback significantly improves acute stroke-management metrics and, thus, represents a potential low-cost strategy for streamlining time-sensitive stroke treatment.